(untitled) (Journal of Enam Medical College, 2012)
Background: It is well known that education level of father and mother is an important factor to achieve breastfeeding. But, according to some literature, there is still controversy that education of parents is really a major factor for perceptions of breastfeeding. Objective: To determine the effects of education level of father and mother on perception or knowledge of breastfeeding. Materials and Methods: This descriptive cross sectional study was conducted in the selected areas of Dhaka city amongst all (202) mothers and fathers of the children of 2 years or more than 2 years of age. Data were collected through pretested questionnaire by face to face interview. Data were analyzed by appropriate univariate analysis. Results: Among the study subjects majority of mothers (49.5%) were of secondary and higher secondary levels and fathers (35.6%) were of graduate and above level of education. Educated mothers (secondary 72% and graduate 90.9%) were more likely to give colostrums to their babies than illiterate mothers (38.9%). Although duration of exclusive breastfeeding and breastfeeding were not associated with maternal education, but knowledge on breastfeeding was highly significant (good knowledge) for higher educated parents (mothers 63.6% and fathers 52.8%) as compared to illiterate or low educated parents (P<0.001). Majority of parents got information from doctors/health workers rather than book or other sources regarding usefulness of breast milk. Conclusion: The study reveals that perceptions of breastfeeding are higher in educated parents than illiterate parents. To reach at an ever satisfactory level of breastfeeding practice, more attention and education need to be given amongst the general people. DOI: http://dx.doi.org/10.3329/jemc.v2i2.12840 J Enam Med Col 2012; 2(2): 67-73